ANALISIS EKONOMI DAN KELEMBAGAAN HUTAN RAKYAT SISTEM AGROFORESTRI KOMBINASI JENIS POHON SERBAGUNA DAN KAKAO : Suatu studi kasus di propinsi Sulawesi Tenggara - R Marsuki Iswandi; Affendi Anwar; B D Nasendi; Hermanto Siregar (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
The agroforestry system is often undertaken by famers in Indonesia specifically for the development of multi purpose tree species in dry land. Farmers use the agroforeftry system because of ils efficient usage of land and labor and to minimize the risk of crop failure.The agroforestry system in Southeast Sulawesi consists of planting cocoa among multi purpose tree species (MPTS), like fruit trees (such as langsat or durian) and coconut trees. The average income earned by farmers who apply the combination of langsat, coconut and cocoa was Rp 2.378.825,-/ha/year. The average income earned by farmers who apply the combination of durian, coconut and cocoa was Rp 2.378.827,-/ha/year. Financially, the agroforestry system with MPTS in Southeast Sulawesi is worth undertaking because it is profitable.From the farmers point of view, the marketing of langsat, durian, coconut and cocoa is not competitive, since farmers are on the weak side in the price information process. The results of the analysis of price transmision elasticity, the index of market integration in the short-run and in the long-run, show that the market for the above mentioned commodities is not integrated. The reason for this is because of the inefficiency and deficiency in the availability of market information.The institutional system in the marketing process of the commodities offered by the farmersis relatively informal. In the marketing process of langsat, durian and coconut, the relationship between farmers and traders can be described as clientelism (patron-client). On the other hand, in the marketing of cocoa, the farmers have a fixed relationship with their market institutions like papalele, whereby the farmers receive working capital from local traders to harvest and to produce and sale the cocoa to the local market.Key words : private forest, agroforestry, MPTS, income, marketing, institution, Southeast Sulawesi.